Answer:
See attachment
Step-by-step explanation:
A) The equations are shown on the attached graph.
x = juice box cost
y = water bottle cost
B) Kara's proposed solution satisfies the first equation, but not the second one.
C) The solution is shown on the attached graph.
____
As a bonus, you get a graph for the other problem you posted. Please note this graph has some issues. Wherever there's a solid line ⌝ or ⌞ the actual shape of the graph should be the opposite one of these.
Answer:
2
Step-by-step explanation:
So I'm going to use vieta's formula.
Let u and v the zeros of the given quadratic in ax^2+bx+c form.
By vieta's formula:
1) u+v=-b/a
2) uv=c/a
We are also given not by the formula but by this problem:
3) u+v=uv
If we plug 1) and 2) into 3) we get:
-b/a=c/a
Multiply both sides by a:
-b=c
Here we have:
a=3
b=-(3k-2)
c=-(k-6)
So we are solving
-b=c for k:
3k-2=-(k-6)
Distribute:
3k-2=-k+6
Add k on both sides:
4k-2=6
Add 2 on both side:
4k=8
Divide both sides by 4:
k=2
Let's check:
:
![3x^2-(3\cdot 2-2)x-(2-6)](https://tex.z-dn.net/?f=3x%5E2-%283%5Ccdot%202-2%29x-%282-6%29)
![3x^2-4x+4](https://tex.z-dn.net/?f=3x%5E2-4x%2B4)
I'm going to solve
for x using the quadratic formula:
![\frac{-b\pm \sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
![\frac{4\pm \sqrt{(-4)^2-4(3)(4)}}{2(3)}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5Cpm%20%5Csqrt%7B%28-4%29%5E2-4%283%29%284%29%7D%7D%7B2%283%29%7D)
![\frac{4\pm \sqrt{16-16(3)}}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5Cpm%20%5Csqrt%7B16-16%283%29%7D%7D%7B6%7D)
![\frac{4\pm \sqrt{16}\sqrt{1-(3)}}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5Cpm%20%5Csqrt%7B16%7D%5Csqrt%7B1-%283%29%7D%7D%7B6%7D)
![\frac{4\pm 4\sqrt{-2}}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5Cpm%204%5Csqrt%7B-2%7D%7D%7B6%7D)
![\frac{2\pm 2\sqrt{-2}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpm%202%5Csqrt%7B-2%7D%7D%7B3%7D)
![\frac{2\pm 2i\sqrt{2}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpm%202i%5Csqrt%7B2%7D%7D%7B3%7D)
Let's see if uv=u+v holds.
![uv=\frac{2+2i\sqrt{2}}{3} \cdot \frac{2-2i\sqrt{2}}{3}](https://tex.z-dn.net/?f=uv%3D%5Cfrac%7B2%2B2i%5Csqrt%7B2%7D%7D%7B3%7D%20%5Ccdot%20%5Cfrac%7B2-2i%5Csqrt%7B2%7D%7D%7B3%7D)
Keep in mind you are multiplying conjugates:
![uv=\frac{1}{9}(4-4i^2(2))](https://tex.z-dn.net/?f=uv%3D%5Cfrac%7B1%7D%7B9%7D%284-4i%5E2%282%29%29)
![uv=\frac{1}{9}(4+4(2))](https://tex.z-dn.net/?f=uv%3D%5Cfrac%7B1%7D%7B9%7D%284%2B4%282%29%29)
![uv=\frac{12}{9}=\frac{4}{3}](https://tex.z-dn.net/?f=uv%3D%5Cfrac%7B12%7D%7B9%7D%3D%5Cfrac%7B4%7D%7B3%7D)
Let's see what u+v is now:
![u+v=\frac{2+2i\sqrt{2}}{3}+\frac{2-2i\sqrt{2}}{3}](https://tex.z-dn.net/?f=u%2Bv%3D%5Cfrac%7B2%2B2i%5Csqrt%7B2%7D%7D%7B3%7D%2B%5Cfrac%7B2-2i%5Csqrt%7B2%7D%7D%7B3%7D)
![u+v=\frac{2}{3}+\frac{2}{3}=\frac{4}{3}](https://tex.z-dn.net/?f=u%2Bv%3D%5Cfrac%7B2%7D%7B3%7D%2B%5Cfrac%7B2%7D%7B3%7D%3D%5Cfrac%7B4%7D%7B3%7D)
We have confirmed uv=u+v for k=2.
Answer:
(n + 4) *2 = 11 * 2
Step-by-step explanation:
(n + 4) *2 = 11 * 2
Divide both sides by 2
![\frac{(n + 4) *2}{2} = \frac{11 * 2}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%28n%20%2B%204%29%20%2A2%7D%7B2%7D%20%3D%20%5Cfrac%7B11%20%2A%202%7D%7B2%7D)
n + 4 = 11
2x+3-5.32=68.82
2x= 71.14
x=35.57
each sneaker costs $35.57